Current Situation of International Fast Fashion Development in China and Analysis of Chinese Consumer Behavior on Fast Fashion - Li, Lina (2019)
In recent years, the development of international fast fashion has gradually slowed down, especially in the Chinese market. The main purpose of this paper is to analyze the development status of international fast fashion in China. This paper mainly analyses the reasons for the slow development of international fast fashion enterprises from four aspects: product upgrading, sustainable development, localization strategy and enterprise ethics. Through the analysis, the paper puts forward some measures that may alleviate the development of international fast fashion in China. Through the study of Chinese consumer behavior, the effectiveness of these measures is verified.